STRATEGI PENJUALAN TERHADAP PIUTANG TIDAK TERTAGIH DIMASA PANDEMI PADA PT. INDUSTRI BAHAN BAKU SEPATU - Yuliana, Indah; Kustiningsih, Nanik (SISTEM Jurnal Ilmu Ilmu Teknik, 2021)
The company's sales strategy of PT. The Shoe Raw Material Industry for uncollectible accounts during the pandemic uses the company's internal control strategy. The research objective is to control management management in the sales aspect as well as to provide recommendations for actions to reduce the risk of uncollectible receivables, so that they can play a role in improving sales performance. The method used is a descriptive study using qualitative methods that describe the decision making on uncollectible accounts. The results showed that the sales internal control strategy of PT. The Shoe Raw Material Industry can be run by considering the accounts receivable aspect. This sales strategy can be an alternative business decision making in the Covid-19 pandemic because it helps companies deal with uncollectible accounts receivable losses.